Psychosocial and Pedagogical Means of Reduction of Hyper Dynamic Manifestations Syndrome Within the Affective Personality Disorder - Liana Novitska (Vasyl Stefanyk Precarpathian National University, 2017)
The problem of correction of affective personality disorders (for example, reducing the manifestations of hyper dynamic syndrome), analyzes the main approaches to its solution. We determined the causes and forms of attention deficit disorder with hyperactivity. To characterize the basic correction means reducing the manifestations of hyper dynamic behavior, which includes two areas with different content and psycho social and recreational components. The first direction is connected with the conduct of an individual or group psycho-correction work; the second - social and recreational include tasks aimed at providing social and psychological support to the individual. It is shown that the problem of hyperactive behavior is determined by the individual variability and natural features caused by human development. Psychological studies suggest the importance of external, social factors, primarily adequate forms of organization and communication, the influence of family relations on the manifestations of hyperactivity. It is shown that the implementation of psycho-pedagogical bases of overcoming hyperactivity leads to increased self-esteem, developing the ability to plan and predict their own behavior and, as a consequence - the disclosure of the individual adaptation possibilities.